Oriented copolymer fiber self-repairing thermal interface composite material and preparation method thereof

By adopting the self-repair technology of orientation copolymer fibers in thermal interface materials, and using the combination of polypyrrole-polyaniline copolymer nanofibers and silicone polymer substrates, the problems of insufficient thermal conductivity and lack of self-repair performance of existing thermal interface materials are solved, and high thermal conductivity, excellent tensile performance and self-repair performance are achieved.

CN119912814APending Publication Date: 2025-05-02WUHAN INSTITUTES OF ADVANCED TECHNOLOGY CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510100266.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing thermal interface materials lack thermal conductivity in high-density integrated electronic devices, and when high thermal conductivity materials are required in specific directions, the anisotropy of the materials cannot effectively meet the needs. At the same time, the poor toughness and lack of self-repairing performance of these materials limit their application scenarios.

Method used

The thermal interface composite material of oriented copolymer fibers is used to improve the thermal conductivity and self-healing properties of the material by converting carbon fibers into one-dimensional conductive nanopolymers and utilizing the π-π conjugation effect between the polymer chains. The material consists of polypyrrole-polyaniline copolymer nanofibers and silicone polymer substrates. It is prepared by electrospinning and arranged in a directional manner in the hot pressing process to form a highly ordered thermally conductive composite material.

Benefits of technology

It achieves a high thermal conductivity, and the thermal conductivity in the fiber orientation direction can reach 6.459W/(m·K). At the same time, the material has excellent tensile performance and self-repair performance, and the resistivity can be as low as 0.115S/cm, which significantly improves the application performance of thermal interface materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912814A_ABST
    Figure CN119912814A_ABST
Patent Text Reader

Abstract

The invention provides an oriented copolymer fiber self-repairing thermal interface composite material, which comprises an organosilicon polymer base material and a one-dimensional copolymer nanofiber, and the copolymer is polypyrrole-polyaniline. Polypyrrole-polyaniline is a high-conductivity one-dimensional copolymer filler, and due to the pi-pi stacking effect of benzene rings in molecules of the copolymer, the conductivity and the electronic heat conduction transmission efficiency are very high. And meanwhile, due to the special one-dimensional structure, one-dimensional copolymer nanofibers with specific orientation can be easily prepared through an electrostatic spinning process, and then the one-dimensional copolymer nanofibers are compounded with an organic silicon polymer base material, so that specific anisotropy is provided for the whole composite material, and the heat conductivity coefficient of the fibers in the orientation direction is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal interface materials, and in particular relates to an oriented copolymer fiber self-repairing thermal interface composite material and a preparation method thereof. Background Art

[0002] The rapid development of science and technology has led to the development of electronic equipment towards lightweight, integration, miniaturization, and multi-functionality. The cooling space of instruments has shrunk and the power density has continued to increase, resulting in uneven heat flow distribution. Local overheating problems have seriously affected the stability and performance of the equipment.

[0003] Thermal interface material is a material widely used in integrated circuit packaging and electronic heat dissipation. It is mainly used to fill the micropores and uneven holes between the heater and the heat sink, thereby eliminating the air gap to increase the effective heat conduction channel, reduce the contact thermal resistance, and improve the heat dissipation efficiency. Polymer materials have the advantages of light weight, good flexibility, outstanding processing performance, good electrical insulation and corrosion resistance, and account for more than 90% of the market share in thermal interface materials. The thermal conductivity of most polymers is concentrated in the range of 0.1 to 0.5 W / (m·K), but the minimum thermal conductivity requirement for thermal interface materials used in high-density integrated electronic devices is 1 W / (m·K).

[0004] At present, most of the thermally conductive composite materials widely used in various fields are filled polymer-based thermally conductive materials. Currently commonly used thermally conductive fillers include inorganic high thermal conductivity fillers including aluminum nitride, boron nitride, etc., and organic thermally conductive fillers are mostly conductive polymers including polyaniline, polythiophene, etc. However, due to the random distribution of polymer fillers in the system, the heat transfer efficiency is still low relying solely on the thermal conductivity of the filler itself, and the actual effect of high thermal conductivity cannot be achieved. In addition, in some special scenarios such as LED lighting and optoelectronic equipment, high thermal conductivity materials in specific directions are urgently needed, and higher thermal conductivity is required in a specific direction. These materials often have anisotropy. Therefore, higher requirements are placed on the preparation and filling methods of thermally conductive fillers.

[0005] CN111978732A discloses a thermal interface material with a three-dimensional heat-conducting network structure, wherein the thermal interface material components include: liquid resin, one-dimensional heat-conducting filler and spherical heat-conducting filler, wherein the one-dimensional heat-conducting filler includes carbon fiber and fibrous nano-carbon heat-conducting material, wherein the axial direction of the carbon fiber is directional and arranged along the thickness direction of the thermal interface material, and the fibrous nano-carbon heat-conducting material exists between the carbon fibers and overlaps with the carbon fibers to form a three-dimensional heat-conducting network structure. However, since the carbon fiber is a brittle material after calcination, the patent results in poor toughness of the composite material and lacks self-repairing properties, resulting in limited application scenarios of this type of thermal interface material, and there is also the problem of being unable to be reused after being damaged. Summary of the invention

[0006] In order to improve the deficiencies of the prior art, the present invention provides the following technical solutions:

[0007] In one aspect, the present invention provides an oriented copolymer fiber self-repairing thermal interface composite material, comprising an organic silicon polymer substrate and one-dimensional copolymer nanofibers, wherein the copolymer is polypyrrole-polyaniline.

[0008] Compared with the prior art, this application transforms carbon fibers into one-dimensional conductive nanopolymers, which not only retains the excellent conductive properties of nanofiber materials, but also retains the high toughness and compatibility of polymers through a simple blending process. In addition, the polymer structure is designed, and the π-π conjugation effect between polymer chains is used to greatly improve the tensile properties and self-healing properties of polymer composites.

[0009] In a specific embodiment of the present application, the mass ratio of the one-dimensional copolymer nanofiber to the silicone polymer substrate is (0.15-0.45):1.

[0010] Preferably, the mass ratio of the one-dimensional copolymer nanofiber to the silicone polymer substrate is (0.2-0.3):1.

[0011] In a specific embodiment of the present application, the length of the one-dimensional copolymer nanofiber is 2 to 100 μm, and the diameter of the fiber is 100 to 500 nm.

[0012] In a specific embodiment of the present application, the one-dimensional copolymer nanofibers are oriented along the axial direction, thereby providing the entire composite material with specific anisotropy, thereby improving the thermal conductivity in the fiber orientation direction.

[0013] In a specific embodiment of the present application, the one-dimensional copolymer nanofibers are distributed along the heat conduction direction in the thermal interface composite material, thereby further improving the anisotropy of the entire composite material, thereby improving the thermal conductivity in the fiber orientation direction.

[0014] In a specific embodiment of the present application, the structural formula of the polypyrrole-polyaniline is:

[0015]

[0016] Among them, PPY is a polypyrrole structural unit, and PANI is a polyaniline structural unit;

[0017] Here, m is a natural number from 20 to 5000, and n and o are each independently a natural number from 50 to 1500.

[0018] In a specific implementation manner of the present application, m is a natural number of 200 to 300, n is a natural number of 50 to 250, and o is a natural number of 500 to 750.

[0019] In the specific implementation of the present application, n and o satisfy n / (n+o)=35-65%; preferably, n and o satisfy n / (n+o)=45-60%. Within this range, PANI has the strongest conductivity and the fastest electron transfer rate, and has the best effect as a thermal conductive filler.

[0020] In the specific implementation of the present application, the m, n, o satisfy m / (m+n+o)=25-75%; preferably, the m, n, o satisfy m / (m+n+o)=40-65%; further preferably, the m, n, o satisfy m / (m+n+o)=50-55%. If it is higher than this range, it is difficult to form a one-dimensional linear structure, and if it is lower than this range, it is difficult for the conductive structure to form an effective network, and the conductive performance is reduced.

[0021] Preferably, the structural formula of the PPY-PANI copolymer (polypyrrole-polyaniline) is:

[0022]

[0023]

[0024] In this application, polypyrrole PPY and polyaniline PANI are both conductive structural units, and their electronic thermal conductivity can further accelerate the heat transfer of the polymer. The thermal conductivity of electrons is usually high, so the electrons in the conductive material can effectively transfer heat, thereby improving the thermal conductivity of the composite material. At the same time, the benzene rings of PPY and PANI have a conjugated effect, providing intermolecular interaction forces and significantly improving the self-healing properties of the thermal conductive material.

[0025] In the present application, both PPY and PANI are polymers with conjugated π electron systems. When PPY and PANI are copolymerized, the polymer chains of the two different structures form a tighter stack, which helps to transfer heat inside the material. If the polymer chains can form an effective heat-conducting network, the heat can be transferred more efficiently along these pathways. Both PPY and PANI contain nitrogen atoms in their repeating units and have similar chemical properties and electrical conductivity. The good compatibility between PPY and PANI can reduce the interfacial thermal resistance between them, making the transfer of heat between the polymer interfaces smoother. In addition, because the chemical properties of the two are similar and can form microphase separation, self-repairing microregions are formed. These microregions can repair cracks by rearranging polymer chains or reorganizing chemical bonds when damage occurs.

[0026] On the other hand, the present application provides a method for preparing the above thermal interface composite material, comprising the following steps:

[0027] S1, dissolving polypyrrole-polyaniline in an organic solvent, and preparing one-dimensional copolymer nanofibers oriented along the axial direction by an electrospinning process;

[0028] S2, aligning the one-dimensional copolymer nanofibers in S1 in a mold, adding liquid polysiloxane and then a curing agent into the mold;

[0029] S3, after standing and curing, the thermal interface composite material is obtained.

[0030] In a specific embodiment of the present application, the step between step S1 and step S2 further includes the following step: subjecting the one-dimensional copolymer nanofibers in step S1 to a hot pressing process to obtain dense one-dimensional copolymer nanofibers.

[0031] Preferably, the process parameters of the hot pressing process include: temperature 90-150° C., pressure 1.5-2.5 MPa, and time 1-6 h.

[0032] In a specific embodiment of the present application, in step S1, the electrospinning process includes at least one of the following technical features:

[0033] (1) The drum speed in the electrospinning process is 15000 to 30000 rpm;

[0034] (2) The distance from the roller to the needle in the electrospinning process is 15 to 20 cm;

[0035] (3) The spinning voltage in the electrospinning process is 1.5 to 2.3 kV;

[0036] (4) The electrospinning time is 3 to 6 hours.

[0037] In a specific embodiment of the present application, in step S1, the mass volume ratio of polypyrrole-polyaniline and organic solvent is (1.2-2.3 g): 10 mL.

[0038] Preferably, in step S1, the mass volume ratio of polypyrrole-polyaniline and organic solvent is (1.5-2.0 g):10 mL.

[0039] In a specific embodiment of the present application, in step S1, the organic solvent is selected from at least one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and dimethyl sulfoxide (DMSO).

[0040] In a specific embodiment of the present application, in step S1, the preparation method of polypyrrole-polyaniline (PPY-PANI) comprises:

[0041] (a) adding an oxidant to deionized water, stirring under a nitrogen atmosphere, and obtaining a mixed solution;

[0042] (b) adding pyrrole monomer to the mixed solution, and stirring and polymerizing at a certain temperature;

[0043] (c) adding aniline monomer to the above solution, and then adding ammonium persulfate to carry out polymerization reaction at a certain temperature;

[0044] (d) After the polymerization reaction is completed, PPY-PANI copolymer is obtained by filtration.

[0045] In a specific embodiment of the present application, the oxidant is selected from at least one of ferric chloride, hydrogen peroxide, ammonium persulfate, cupric chloride, and potassium permanganate.

[0046] In a specific embodiment of the present application, the stirring temperature in step (b) is 30-50° C., and the stirring time is 2-8 h; preferably, the stirring time is 5-8 h.

[0047] In a specific embodiment of the present application, the stirring temperature in step (c) is -10 to 10°C, and the stirring time is 3 to 24 hours; preferably, the stirring time is 4 to 18 hours.

[0048] In a specific embodiment of the present application, in step S2, the specific method of directional arrangement in the mold is: after the one-dimensional copolymer nanofiber is cut into several sections with a knife, the sections are arranged in one direction and placed in the mold.

[0049] In a specific embodiment of the present application, in step S2, the polysiloxane is an alkoxy-terminated polysiloxane.

[0050] Preferably, the polysiloxane is at least one of methyldimethoxy-terminated polysiloxane, ethyldimethoxy-terminated polysiloxane, vinyldimethoxy-terminated polysiloxane, and propyldimethoxy-terminated polysiloxane.

[0051] In a specific embodiment of the present application, in step S2, the mass ratio of the one-dimensional copolymer nanofiber to polysiloxane is (0.15-0.45):1.

[0052] Preferably, in step S2, the mass ratio of the one-dimensional copolymer nanofibers to polysiloxane is (0.2-0.3):1.

[0053] In a specific embodiment of the present application, in step S2, the curing agent is selected from at least one of tetraisopropyl titanate, dimethyl tin, phenyl tin, and triphenyl tin.

[0054] In a specific embodiment of the present application, in step S2, the mass ratio of the curing agent to the polysiloxane is (0.01-0.04):1.

[0055] Preferably, in step S2, the mass ratio of the curing agent to the polysiloxane is (0.02-0.035):1.

[0056] In a specific embodiment of the present application, in step S3, the curing refers to curing in air for 36-96 hours.

[0057] In step S1 of the present application, axially oriented one-dimensional copolymer nanofibers are prepared by an electrospinning process. In this process, the rotation speed is increased to pull the arrangement direction of the nanofibers so that the traction force and the electric field force overcome the gravity, thereby oriented the nanofibers along the axial direction.

[0058] Beneficial effects:

[0059] (1) The self-repairing thermal interface material of the present invention uses oriented one-dimensional copolymer nanofibers as fillers, has high order, and has a high thermal conductivity in the horizontal direction, which can reach 6.459 W / (m·K);

[0060] (2) The present invention is a thermally conductive composite material of a full polymer system. Different from the traditional method of adding inorganic thermally conductive fillers, this polymer system has the characteristics of softness and excellent tensile elongation at break;

[0061] (3) The self-healing thermal interface material of the present invention also has high electrical conductivity, and the resistivity can be as low as 0.115S / cm. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 The scanning electron microscope image of the one-dimensional oriented nanofibers of PPY-PANI prepared in Example 1 of the present invention is DETAILED DESCRIPTION

[0063] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0064] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0065] In the description of the present invention, it should be noted that the terms "comprises", "includes" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.

[0066] Traditional polymer composite thermal interface materials have low heat conduction efficiency due to the irregular and random distribution of fillers in the system. At the same time, due to the small difference in thermal conductivity in all directions of its isotropy, it cannot be applied to thermal interface management materials with high thermal conductivity requirements and specific directions. In order to solve this problem, the present application starts with the chemical structure and arrangement of polymer fillers, and first synthesizes a highly conductive one-dimensional copolymer filler of polypyrrole-polyaniline. Due to the π-π stacking effect of benzene rings in the molecule, the electrical conductivity and electronic thermal conductivity transmission efficiency of the copolymer are very high. At the same time, due to its special one-dimensional structure, it is easy to prepare into a one-dimensional copolymer nanofiber with a specific orientation through an electrospinning process, and then composited with a silicone polymer substrate to provide a specific anisotropy to the entire composite material, thereby improving the thermal conductivity in the fiber orientation direction.

[0067] To this end, the present invention provides an oriented copolymer fiber self-repairing thermal interface composite material and a preparation method thereof, wherein the preparation method comprises three steps of synthesizing a polypyrrole-polyaniline copolymer, preparing copolymer nanofibers, and preparing a self-repairing thermal interface material, specifically:

[0068] Step 1, Synthesis of polypyrrole-polyaniline (PPY-PANI) copolymer

[0069] Add 0.02-0.1 g of oxidant to 100 mL of deionized water and stir for 15-20 min under nitrogen atmosphere;

[0070] Add 1-5 mL of pyrrole monomer to the above mixed solution, and stir and polymerize at 30-50° C. for 2-8 hours;

[0071] Add 5.6-13.5g of aniline monomer to the above solution, add 1.3-3.3g of ammonium persulfate, carry out polymerization reaction at -10-10°C for 3-24h, and then pour out the product;

[0072] The product was filtered and washed repeatedly with pure water for 3 to 6 times to obtain a PPY-PANI copolymer.

[0073] Preferably, the amount of the oxidant is 0.05 to 0.08 g;

[0074] Preferably, the amount of the pyrrole monomer is 1.5 to 2.5 mL;

[0075] Preferably, the amount of the aniline monomer is 6 to 9.5 g;

[0076] Preferably, the amount of ammonium persulfate used is 1.5 to 2.8 g.

[0077] Step 2: Preparation of PPY-PANI copolymer nanofibers

[0078] Dissolve 1.2-2.3 g of the PPY-PANI copolymer prepared above in 10 mL of DMF solvent;

[0079] Oriented nanofibers were prepared by electrospinning, and the specific process parameters were as follows: voltage of 1.5-2.3 KV, drum speed of 15000-30000 rpm, distance from drum to needle of 15-20 cm, spinning process of 3-6 hours, in which the arrangement direction of nanofibers was pulled by increasing the speed, so that the pulling force and electric field force overcame gravity and the nanofibers were oriented along the axial direction;

[0080] The prepared nanofibers were hot pressed at 120° C. and 2.0 MPa for 2 h to obtain dense one-dimensional copolymer nanofibers.

[0081] Preferably, the amount of the PPY-PANI copolymer is 1.5 to 2.0 g;

[0082] Preferably, the electrospinning voltage is 1.8-2.0 KV;

[0083] Preferably, the drum speed in the electrospinning process is 17000-30000 rpm;

[0084] Preferably, the spinning process of the electrospinning process is 4 to 6 hours.

[0085] Step 3: Preparation of self-repairing thermal interface material

[0086] 1.5 to 4.5 g of the one-dimensional copolymer nanofibers prepared as above are collected from the drum and arranged in one direction in a polytetrafluoroethylene mold. 10 g of liquid polysiloxane and then 0.1 to 0.4 g of a curing agent are added to the mold. After standing and curing in air for 48 hours, the self-healing thermal interface composite material is obtained.

[0087] Preferably, the one-dimensional copolymer nanofiber is used in an amount of 2.0 to 3.0 g;

[0088] Preferably, the amount of the curing agent used is 0.2 to 0.35 g.

[0089] The present invention is further described in detail below through specific embodiments.

[0090] The reagents and materials described in the following examples, unless otherwise specified, can be obtained from commercial sources. Among them, the silicone oil (alkoxy-terminated polysiloxane) model is M934239, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0091] Example 1

[0092] (1) Add 0.05 g of ammonium persulfate to 100 mL of deionized water and stir under nitrogen atmosphere for 15 min;

[0093] (2) adding 2.5 mL of pyrrole monomer to the above mixed solution, and stirring and polymerizing at 40° C. for 5 h;

[0094] (3) Then, 9.5 g of aniline monomer was added to the above solution, and 2.4 g of ammonium persulfate was added. After the polymerization reaction was carried out at 0° C. for 8 h, the product was poured out.

[0095] (4) The product was filtered and washed with purified water for 5 times to obtain a PPY-PANI copolymer;

[0096] The structural formula of the obtained PPY-PANI copolymer is as follows:

[0097]

[0098] (5) Dissolve 1.8 g of the PPY-PANI prepared above in 10 mL of DMF solvent;

[0099] (6) Oriented nanofibers were prepared by electrospinning. The specific process parameters were as follows: voltage 1.8 KV, drum speed 25000 rpm, distance from the drum to the needle 15 cm, and spinning time 4 h. The SEM image of the obtained oriented nanofibers is shown in Figure 1 As shown, it can be seen from the figure that the polymer nanofibers are oriented in one direction.

[0100] (7) The prepared nanofibers were then hot pressed at 120°C and 2.0 MPa for 2 h to obtain dense one-dimensional oriented conductive nanofibers.

[0101] (8) After removing the 3.0 g of nanofibers obtained above from the drum, they were placed in a polytetrafluoroethylene mold along one direction, and then 10 g of alkoxy-terminated polysiloxane was added so that the fibers were immersed in silicone oil. Then 0.2 g of tetraisopropyl titanate was added dropwise, and after standing and curing in air for 48 hours, a thermally conductive composite nanomaterial was obtained.

[0102] Example 2

[0103] (1) Add 0.08 g of ammonium persulfate to 100 mL of deionized water and stir under nitrogen atmosphere for 15 min;

[0104] (2) adding 2.5 mL of pyrrole monomer to the above mixed solution, and polymerizing at 50° C. under stirring for 8 h;

[0105] (3) Then, 8.6 g of aniline monomer was added to the above solution, and 2.8 g of ammonium persulfate was added. After the polymerization reaction was carried out at 10° C. for 4 h, the product was poured out;

[0106] (4) The product was filtered and washed with purified water for 5 times to obtain a PPY-PANI copolymer;

[0107] The structural formula of the obtained PPY-PANI copolymer is as follows:

[0108]

[0109] (5) Dissolve 1.5 g of the PPY-PANI prepared above in 10 mL of DMF solvent;

[0110] (6) Oriented nanofibers were prepared by electrospinning process. The specific process parameters were as follows: voltage of 2.0 KV, drum speed of 17000 rpm, distance from drum to needle of 18 cm, and spinning time of 5 h.

[0111] (7) The prepared nanofibers were then hot pressed at 120°C and 2.0 MPa for 2 h to obtain dense one-dimensional oriented conductive nanofibers.

[0112] (8) After taking the 2.0 g of nanofibers obtained above off the drum, they were placed in a polytetrafluoroethylene mold along one direction, and then 10 g of alkoxy-terminated polysiloxane was added so that the fibers were immersed in silicone oil. Then 0.25 g of tetraisopropyl titanate was added dropwise, and after standing and curing in air for 48 hours, a thermally conductive composite nanomaterial was obtained.

[0113] Example 3

[0114] (1) Add 0.07 g of ammonium persulfate to 100 mL of deionized water and stir under nitrogen atmosphere for 15 min;

[0115] (2) adding 1.5 mL of pyrrole monomer to the above mixed solution, and stirring and polymerizing at 30° C. for 8 h;

[0116] (3) Then, 6.0 g of aniline monomer was added to the above solution, and 1.5 g of ammonium persulfate was added. After the polymerization reaction was carried out at -10°C for 18 hours, the product was poured out;

[0117] (4) The product was filtered and washed with purified water for 5 times to obtain a PPY-PANI copolymer;

[0118] The structural formula of the obtained PPY-PANI copolymer is as follows:

[0119]

[0120] (5) Dissolve 2.0 g of the PPY-PANI prepared above in 10 mL of DMF solvent;

[0121] (6) Oriented nanofibers were prepared by electrospinning process. The specific process parameters were as follows: voltage was 1.8 KV, drum speed was 30000 rpm, distance from drum to needle was 20 cm, and spinning process was 6 h.

[0122] (7) The prepared nanofibers were then hot pressed at 120°C and 2.0 MPa for 2 h to obtain dense one-dimensional oriented conductive nanofibers.

[0123] (8) After taking the 2.0 g of nanofibers obtained above off the drum, they were placed in a polytetrafluoroethylene mold along one direction, and then 10 g of alkoxy-terminated polysiloxane was added so that the fibers were immersed in silicone oil. Then 0.35 g of tetraisopropyl titanate was added dropwise, and after standing and curing in air for 48 hours, a thermally conductive composite nanomaterial was obtained.

[0124] Comparative Example 1

[0125] Compared with Example 1, the only difference is that the filler is PPY homopolymer instead of PPY-PANI copolymer. The specific steps are:

[0126] (1) Add 0.05 g of ammonium persulfate to 100 mL of deionized water and stir under nitrogen atmosphere for 15 min;

[0127] (2) adding 2.5 mL of pyrrole monomer to the above mixed solution, and stirring and polymerizing at 40° C. for 5 h;

[0128] (3) The product was filtered and washed with purified water for 5 times to obtain a PPY homopolymer.

[0129] (5) Dissolve 1.8 g of the PPY homopolymer prepared above in 10 mL of DMF solvent;

[0130] (6) Oriented nanofibers were prepared by electrospinning process. The specific process parameters were as follows: voltage was 1.8 KV, drum speed was 25000 rpm, distance from drum to needle was 15 cm, and spinning process was 4 h.

[0131] (7) The prepared nanofibers were then hot pressed at 120°C and 2.0 MPa for 2 h to obtain dense one-dimensional oriented conductive nanofibers.

[0132] (8) After removing the 3.0 g of nanofibers obtained above from the drum, they were placed in a polytetrafluoroethylene mold along one direction, and then 10 g of alkoxy-terminated polysiloxane was added so that the fibers were immersed in silicone oil. Then 0.2 g of tetraisopropyl titanate was added dropwise, and after standing and curing in air for 48 hours, a thermally conductive composite nanomaterial was obtained.

[0133] Comparative Example 2

[0134] Compared with Example 1, the only difference is that the filler is a PANI homopolymer instead of a PPY-PANI copolymer. The specific steps are:

[0135] (1) Add 0.05 g of ammonium persulfate to 100 mL of deionized water and stir under nitrogen atmosphere for 15 min;

[0136] (2) Then, 9.5 g of aniline monomer was added to the above solution, and 2.4 g of ammonium persulfate was added. After the polymerization reaction was carried out at 0° C. for 8 h, the product was poured out.

[0137] (3) The product was filtered and washed with pure water for 5 times to obtain PANI homopolymer.

[0138] (5) Dissolve 1.8 g of the PANI homopolymer prepared above in 10 mL of DMF solvent;

[0139] (6) Oriented nanofibers were prepared by electrospinning process. The specific process parameters were as follows: voltage was 1.8 KV, drum speed was 25000 rpm, distance from drum to needle was 15 cm, and spinning process was 4 h.

[0140] (7) The prepared nanofibers were then hot pressed at 120°C and 2.0 MPa for 2 h to obtain dense one-dimensional oriented conductive nanofibers.

[0141] (8) After removing the 3.0 g of nanofibers obtained above from the drum, they were placed in a polytetrafluoroethylene mold along one direction, and then 10 g of alkoxy-terminated polysiloxane was added so that the fibers were immersed in silicone oil. Then 0.2 g of tetraisopropyl titanate was added dropwise, and after standing and curing in air for 48 hours, a thermally conductive composite nanomaterial was obtained.

[0142] Comparative Example 3

[0143] Compared with Example 1, the only difference is that the anisotropic oriented nanofibers are not prepared by electrospinning process, but the isotropic copolymer filler is directly obtained by hot pressing process. The specific steps are:

[0144] (1) Add 0.05 g of ammonium persulfate to 100 mL of deionized water and stir under nitrogen atmosphere for 15 min;

[0145] (2) adding 2.5 mL of pyrrole monomer to the above mixed solution, and stirring and polymerizing at 40° C. for 5 h;

[0146] (3) Then, 9.5 g of aniline monomer was added to the above solution, and 2.4 g of ammonium persulfate was added. After the polymerization reaction was carried out at 0° C. for 8 h, the product was poured out.

[0147] (4) The product was filtered and washed with purified water for 5 times to obtain a PPY-PANI copolymer;

[0148] (5) The prepared PPY-PANI copolymer was hot pressed at 120° C. and 2.0 MPa for 2 h to obtain an isotropic copolymer material.

[0149] (6) 3.0 g of the isotropic film obtained above was immersed in 10 g of alkoxy-terminated polysiloxane, then placed in a polytetrafluoroethylene mold, 0.2 g of tetraisopropyl titanate was added dropwise, and after standing and curing in air for 48 hours, a thermally conductive composite nanomaterial was obtained.

[0150] Comparative Example 4

[0151] Compared with Example 1, the only difference is that the drum speed is higher in the electrospinning process. The specific steps are:

[0152] (1) Add 0.05 g of ammonium persulfate to 100 mL of deionized water and stir under nitrogen atmosphere for 15 min;

[0153] (2) adding 2.5 mL of pyrrole monomer to the above mixed solution, and stirring and polymerizing at 40° C. for 5 h;

[0154] (3) Then, 9.5 g of aniline monomer was added to the above solution, and 2.4 g of ammonium persulfate was added. After the polymerization reaction was carried out at 0° C. for 8 h, the product was poured out.

[0155] (4) The product was filtered and washed with purified water for 5 times to obtain a PPY-PANI copolymer;

[0156] (5) Dissolve 1.8 g of the PPY-PANI prepared above in 10 mL of DMF solvent;

[0157] (6) Oriented nanofibers were prepared by electrospinning process. The specific process parameters were as follows: voltage was 1.8 KV, drum speed was 35000 rpm, distance from drum to needle was 15 cm, and spinning process was 4 h.

[0158] (7) The prepared nanofibers were then hot pressed at 120°C and 2.0 MPa for 2 h to obtain dense one-dimensional oriented conductive nanofibers.

[0159] (8) After the 3.0 g of nanofibers obtained above were taken off the drum, they were placed in a polytetrafluoroethylene mold along one direction, and then 10 g of alkoxy-terminated polysiloxane was added so that the fibers were immersed in silicone oil. Then 0.2 g of tetraisopropyl titanate was added dropwise, and after standing and curing in air for 48 hours, a thermally conductive composite nanomaterial was obtained.

[0160] Comparative Example 5

[0161] Compared with Example 1, the only difference is that the drum speed is lower in the electrospinning process. The specific steps are:

[0162] (1) Add 0.05 g of ammonium persulfate to 100 mL of deionized water and stir under nitrogen atmosphere for 15 min;

[0163] (2) adding 2.5 mL of pyrrole monomer to the above mixed solution, and stirring and polymerizing at 40° C. for 5 h;

[0164] (3) Then, 9.5 g of aniline monomer was added to the above solution, and 2.4 g of ammonium persulfate was added. After the polymerization reaction was carried out at 0° C. for 8 h, the product was poured out.

[0165] (4) The product was filtered and washed with purified water for 5 times to obtain a PPY-PANI copolymer;

[0166] (5) Dissolve 1.8 g of the PPY-PANI prepared above in 10 mL of DMF solvent;

[0167] (6) Oriented nanofibers were prepared by electrospinning process. The specific process parameters were as follows: voltage was 1.8 KV, drum speed was 10000 rpm, distance from drum to needle was 15 cm, and spinning process was 4 h.

[0168] (7) The prepared nanofibers were then hot pressed at 120°C and 2.0 MPa for 2 h to obtain dense one-dimensional oriented conductive nanofibers.

[0169] (8) After the 3.0 g of nanofibers obtained above were taken off the drum, they were placed in a polytetrafluoroethylene mold along one direction, immersed and then added into 10 g of alkoxy-terminated polysiloxane so that the fibers were immersed in silicone oil. Then, they were placed in a polytetrafluoroethylene mold, 0.2 g of tetraisopropyl titanate was added dropwise, and after standing and curing in air for 48 hours, a thermally conductive composite nanomaterial was obtained.

[0170] The self-repairing thermal interface materials obtained in the above examples and comparative examples were tested for thermal conductivity, electrical properties, tensile properties and self-repairing properties, specifically:

[0171] Thermal conductivity test

[0172] Samples with a diameter of 3 cm and thicknesses of 1 mm, 2 mm and 3 mm were prepared, and the thermal conductivity of the samples was measured using a thermal conductivity tester. The results are shown in Table 1.

[0173] Electrical performance test

[0174] The composite material to be tested was prepared into a 2 mm thick cylinder, and the resistivity of the composite material was tested using a four-probe tester.

[0175] Tensile properties test

[0176] The product to be tested is prepared into a bone-shaped sample, and its tensile properties are tested using a universal testing machine at a speed of 10 mm / min.

[0177] Self-healing performance test

[0178] (1) Thermal conductivity

[0179] The samples were prepared with a diameter of 3 cm and thicknesses of 1 mm, 2 mm and 3 mm, and their thermal conductivity was measured as the initial value. The samples of three thicknesses were cut with a knife, and the thermal conductivity was measured and calculated 24 hours after self-repair, recorded as the value after repair, and calculated by the ratio of the two, thermal conductivity repair efficiency = value after repair / initial value*100%.

[0180] (2) Tensile properties

[0181] The sample was prepared into a bone-shaped sample, and its tensile properties were tested at a speed of 10 mm / min using a universal testing machine, which was recorded as the initial value. The sample was cut in the middle with a knife, and the cuts were put together. After 24 hours at room temperature, its tensile properties were tested at a speed of 10 mm / min using a universal testing machine, which was recorded as the repaired value. Mechanical self-repair efficiency = repaired value / initial value*100%.

[0182] Table 1

[0183]

[0184] It can be seen from the table that the lateral thermal conductivity of the embodiment is significantly better than that of the comparative example, showing the anisotropy of the material, indicating that the conjugated structure of the polymer has a great influence on the thermal conductivity of the composite material, and proving that the electron transfer thermal conduction mode can effectively improve the thermal interface management ability of the material.

[0185] The specific embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0186] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0187] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. An oriented copolymer fiber self-repairing thermal interface composite material, characterized in that: The invention comprises an organic silicon polymer substrate and one-dimensional copolymer nanofibers, wherein the copolymer is polypyrrole-polyaniline.

2. The thermal interface composite material according to claim 1, characterized in that: The mass ratio of the one-dimensional copolymer nanofiber to the silicone polymer substrate is (0.15-0.45):1; Preferably, the one-dimensional copolymer nanofiber has a length of 2 to 100 μm and a fiber diameter of 100 to 500 nm.

3. The thermal interface composite material according to claim 1, characterized in that: The one-dimensional copolymer nanofibers are oriented along the axial direction; Preferably, the one-dimensional copolymer nanofibers are distributed along the heat conduction direction in the thermal interface composite material.

4. The thermal interface composite material according to claim 1, characterized in that: The structural formula of the polypyrrole-polyaniline is: Among them, PPY is a polypyrrole structural unit, and PANI is a polyaniline structural unit; Here, m is a natural number from 20 to 5000, and n and o are each independently a natural number from 50 to 1500.

5. The thermal interface composite material according to claim 4, characterized in that: m is a natural number from 200 to 300, n is a natural number from 50 to 250, and o is a natural number from 500 to 750; Preferably, the n and o satisfy n / (n+o)=35-65%; Preferably, the m, n, and o satisfy m / (m+n+o)=25-75%.

6. The method for preparing the thermal interface composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, dissolving polypyrrole-polyaniline in an organic solvent, and preparing one-dimensional copolymer nanofibers oriented along the axial direction by an electrospinning process; S2, aligning the one-dimensional copolymer nanofibers in S1 in a mold, adding liquid polysiloxane and then a curing agent into the mold; S3, after standing and curing, the thermal interface composite material is obtained.

7. The preparation method according to claim 6, characterized in that: The step between step S1 and step S2 also includes the following steps: subjecting the one-dimensional copolymer nanofibers in step S1 to a hot pressing process to obtain dense one-dimensional copolymer nanofibers; Preferably, the process parameters of the hot pressing process include: temperature 90-150° C., pressure 1.5-2.5 MPa, and time 1-6 h.

8. The preparation method according to claim 6, characterized in that: The drum speed in the electrospinning process is 15000-30000 rpm; Preferably, in the electrospinning process, the distance from the roller to the needle is 15 to 20 cm.

9. The preparation method according to claim 6, characterized in that: The spinning voltage in the electrospinning process is 1.5 to 2.3 KV; Preferably, the electrospinning time is 3 to 6 hours.

10. The preparation method according to claim 6, characterized in that: The organic solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide; Preferably, the curing agent is selected from at least one of tetraisopropyl titanate, dimethyl tin, phenyl tin and triphenyl tin.

Citation Information

Patent Citations

  • Thermal interface material with three-dimensional thermally conductive network structure

    CN111978732A